Iowa Birdline update for November 25, 1991 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1991)
Email of Iowa Birdline updates for November 25, 1991. The highlights for the update include sightings of a White-winged Scoter, Long-tailed Duck, Glaucous, Thayer's and Lesser Black-backed Gulls. Also included are handwritten notes with sightings of a Northern Saw-whet Owl, Brown Thrasher and a Merlin. Epson - sheet feed/flatbed